Ecotourism Of Bonjeruk Tourism Village - Jumhur Hakim; Rahman; Kertajadi; Taufan Handika Putra (Jurnal Internasional Riset Bisnis Pariwisata, 2022)
Bonjeruk tourist village with Nostalgia Tourism Branding develops Cultural and historical Tourism Products, Rural Nature and Culinary which will give an impression to visitors how to live peacefully in the countryside with beautiful natural nuances and noble culture so that they will feel comfortable after all this time busy with the hustle and bustle of life in the area of origin. The data collection methods used in this research are observation, interview, and documentation, data analysis in this research is descriptive qualitative. Based on the results of the research conducted, Bonjeruk village ecotourism has a variety of tourism potential that is beautiful and interesting to visit, the potential of ecotourism includes tourists can do English learning activities, enjoy rice fields and enjoy the agricultural products of the local community, one of which is coffee. The next potential is to enjoy the historic buildings of Dutch heritage.